Spatiotemporal Changes of the Environmental DNA Concentrations of Amphidromous Fish Plecoglossus altivelis altivelis in the Spawning Grounds in the Takatsu River, Western Japan - Inui, Ryutei; Akamatsu, Yoshihisa; Kono, Takanori; Saito, Minoru; Miyazono, Seiji; Nakao, Ryohei (Frontiers in Ecology and Evolution, 2021)
The Ayu Plecoglossus altivelis altivelis is an amphidromous fish that is not only the most important commercial fishery species in Japanese rivers but also has a high economic value in recreational fishing. However, the degradation of its spawning grounds has caused a decrease in its abundance. In this study, we used environmental DNA (eDNA) to monitor the Ayu in the Takatsu River in Japan to (1) identify the spawning season in three known spawning grounds, (2) clarify changes in the main spawning grounds during the spawning season, and (3) discover unknown spawning grounds. We collected 1 L of the surface river water at three known spawning grounds nine times in 2018 and seven times in 2019 in the lower reaches of the Takatsu River. We also collected samples from seven unknown sites in 2018. The water samples were filtered through glass fiber filters. Total eDNA was extracted from each filtered sample and a Real-time quantitative PCR was performed with the specific primers and probe for Ayu. The results of the eDNA analyses showed that (1) the spawning season was in November in 2018 and in September in 2019. (2) One site was used as a spawning ground in both the early and the late spawning season, depending on the year. At the second site, the frequency of use changed year by year. The third site was the main spawning ground in the middle to late spawning season every year. From these results, we elucidated that some spawning grounds are used regularly every year, while the use of others varies year by year. (3) In five of the seven unknown sites, the nighttime eDNA concentrations were high at least once during the four surveys, suggesting that these sites may have functioned as spawning grounds. In particular, one site could be an important new spawning ground.